Efektivitas Pelaksanaan Bantuan Hukum bagi Masyarakat Kurang Mampu oleh Lembaga Bantuan Hukum Jakarta - Fauzan Fadly Somar; Megawati Barthos; Indah Kusuma Wardhani (Universitas Borobudur, 2023)
The enactment of Law Number 16 of 2011 concerning Legal Aid has become the basis for the state to guarantee its citizens, especially the poor, to get access to justice and equality before the law. However, the provision of legal aid has not touched the poor much so that they have difficulty accessing justice. Therefore, this study will discuss the effectiveness of the implementation of legal aid for the poor by LBH Jakarta. The method used in this research is normative juridical and empirical juridical. The results of the study show that the implementation of legal aid for the poor by LBH Jakarta is still ineffective due to limited human resources, where the number of public lawyers is very small which is not proportional to the large number of cases that must be handled each year. This has resulted in not all cases being handled directly by public lawyers at LBH Jakarta.